2021
DOI: 10.1038/s41467-021-21719-x
|View full text |Cite
|
Sign up to set email alerts
|

Singlet exciton fission in a modified acene with improved stability and high photoluminescence yield

Abstract: We report a fully efficient singlet exciton fission material with high ambient chemical stability. 10,21-Bis(triisopropylsilylethynyl)tetrabenzo[a,c,l,n]pentacene (TTBP) combines an acene core with triphenylene wings that protect the formal pentacene from chemical degradation. The electronic energy levels position singlet exciton fission to be endothermic, similar to tetracene despite the triphenylenes. TTBP exhibits rapid early time singlet fission with quantitative yield of triplet pairs within 100 ps follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…Strikingly, we even observe similar triplet features—polarization pattern and spectral width—in H-like film 2 , which shows no evidence for SF and no detectable optical signatures of triplet formation. Because of this surprising behavior, we additionally considered the role of orientation of both samples relative to the external magnetic field, which has been shown to impact the trEPR spectra of triplets in other SF materials 73 . In neither film did we observe the appearance of SF spectral signatures at other angles.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, we even observe similar triplet features—polarization pattern and spectral width—in H-like film 2 , which shows no evidence for SF and no detectable optical signatures of triplet formation. Because of this surprising behavior, we additionally considered the role of orientation of both samples relative to the external magnetic field, which has been shown to impact the trEPR spectra of triplets in other SF materials 73 . In neither film did we observe the appearance of SF spectral signatures at other angles.…”
Section: Resultsmentioning
confidence: 99%
“…[45] Congreve et al demonstrated that the SF process could cross the external quantum efficiency over the unity of OSCs. [46] There are a few materials have been reported for SF application in the literature called polydiacetylene, [47] carotenoids, [48] pentacene, [49] tetracene, [50] anthracene, [51] and 10,21-bis(tri-isopropylsilylethynyl) tetrabenzo[a,c,l,n] pentacene, [52] and so forth, and it is very challenging to find the right material. The spectral converter materials were introduced in the solar cells to assist the higher to lower photons energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to increased interest in the engineering of the properties of single molecules and molecular aggregates via chemical modification. In the context of a rational design of SF chromophores, several key parameters have been identified, such as electronic coupling strength, molecular arrangement, and the energetic difference of singlet and triplet states. Current approaches toward an optimization of SF chromophores employ, for example, the addition of bulky side groups to modify the molecular packing in aggregates , or the use of dimers of SF chromophores for a controlled variation of the relative molecular arrangement and, thus, of the electronic coupling strength. Alternatively, the energy difference between singlet and triplet states has been modified by the substitution of carbon atoms of the SF chromophore backbone with heteroatoms, such as nitrogen or sulfur, or by fluorination of the SF chromophore. The latter is in the general context of the optimization of organic semiconductors for optoelectronic devices, a well-established approach to increase stability against oxidation or to control energy levels, molecular packing, and charge transport. …”
mentioning
confidence: 99%